Financial Sector-Specific Determinants of Foreign Direct Investment in Nepal - Sapkota, Bijaya (Economic Review of Nepal, 2020)
This study examines and analyses the impact of financial sector-specific determinants on FDI inflow to Nepal. The Engle-Granger cointegration and error correction models were employed to test the long-run and short-run relationships between the dependent and independent variables using the time series data from 1994 to 2020. The Augmented Dicky Fuller (ADF) test was adopted to test the stationarity of the variables. Similarly, the Breusch-Godfrey serial correlation LM test, the Breusch-Pagan-Godfrey test, the VIF test, and the CUSUM of the square test were employed to detect the presence of autocorrelation, heteroscedasticity, multicollinearity, and the stability of the model. The study's findings revealed a negative significant relation between the NEPSE index and the FDI inflow to Nepal in the short run. All other independent variables are insignificant with FDI inflow in the short run. Similarly, interest rate, broad money supply (M2), and inflation positively correlate with FDI in the long run while the NEPSE index is insignificant in the long run. Broad money supply is found to have the strongest impact on FDI inflow among the independent variables. The study's findings suggest that policymakers should keep increasing the money supply at a stable and sustainable rate maintaining a moderate level of inflation and interest rate in the economy to attract a significant amount of FDI in the fiscal years to come.